Growth, extraction and assay methods for the enzymes ornithine transcarbamylase, aspartate transcarbamylase and carbamyl phosphokinase from Neurospora - R. H. Davis (Fungal Genetics Reports, 1965)
Growth, extraction and assay methods for the enzymes ornithine transcarbamylase, aspartate transcarbamylase and carbamyl phosphokinase from Neurospora